HUMAN RESOURCES COMPETENCE MODEL AND INTERNAL CONTROL SYSTEM IN VILLAGE GOVERNANCE, REPORT QUALITY AND ACCOUNTABILITY - Rahman, Yudi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study was to determine the effect of human resource competence, internal control systems on the quality of village government financial reports, and the influence of human resource competencies, internal control systems on accountability and the quality of village government financial reports affect accountability. This research model will be analyzed using the Partial Least Square (PLS) method and assisted with Smart PLS 3.0 software. PLS is an alternative method of Structural Equation Modeling (SEM). The population in this study is a village in the province of South Kalimantan, Tabalong Regency 16 Villages to be used as populations in research and samples in research as many as 16 x 3 apparatus or Deesa apparatus, totaling 48 apparatus. The results of the study show that Human Resource Competence influences the Quality of Village Government Financial Reports. The internal control system influences the quality of village government financial reports. Human Resource Competence influences Accountability. The internal control system influences accountability, and the quality of village government financial reports affects accountability.